CSR Trough the Internet: The Case of Italy - Stefano Amelio; Claudio Battistini (European Scientific Journal, ESJ, 2018)
The aim of the paper is to analyze the level of acceptance of social responsibility practices in Italy and in particular to evaluate the degree of social responsibility arising from the websites of Italian listed companies. CSR communication contributes to a corporation’s corporate social disclosure, whose main purpose is to enhance a corporate image in order to promote customer and community relations and indirectly promote products to customers. To reach this goal, transparency is crucial. However transparency in the field of CSR is a difficult matter for two reasons: there is not uniformity in social reporting and the preparation of this document is not mandatory. The research is divided into two sections and the approach used is mainly descriptive: in the first part the concept of social balance as a means to interact with all the stakeholders of a firm is exposed. In the second part the paper analyses the web sites of a panel of selected listed Italian companies. The data are able to demonstrate that the size of the company still represent a barrier to CSR reporting and communication since require efforts and investment in term of time and resources. The research also shows that those company identified as “best practice” in the selected panel have a common strength: they attach an importan role to CSR in their corporate websites as a way to improve their image from the perspective of the multiple stakeholders.